2016
DOI: 10.1177/1555343416672557
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of In-Game Communication as an Indicator of Recognition Primed Decision Making in Elite Australian Rules Football Umpires

Abstract: In sport, decision-making research has identified consistent results among the three variations of the recognition primed decision (RPD) model. Despite the fact that officials in sport are a key component of sports systems, previous research has explored the RPD model in players only. This paper addresses this by applying the RPD model to examine the decision making of umpires in Australian Rules football (Australian Football League [AFL]). Method: Audible communication instances of AFL field umpiring teams ov… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 25 publications
1
8
0
1
Order By: Relevance
“…Salient features constitute properties of the situation that can lead experts to recognize the situations as familiar or unfamiliar. Previous qualitative studies investigated the recognition processes team sport experts used, in Australian Football (Neville et al, 2017), volleyball (Macquet, 2009), soccer (Kermarrec and Bossard, 2014), and ice hockey (Bossard et al, 2010;Mulligan et al, 2012). At least 80% of the experts' decisions were classified as simple-matching, which is consistent with the results of Klein' studies in work fields.…”
Section: Introductionsupporting
confidence: 73%
See 1 more Smart Citation
“…Salient features constitute properties of the situation that can lead experts to recognize the situations as familiar or unfamiliar. Previous qualitative studies investigated the recognition processes team sport experts used, in Australian Football (Neville et al, 2017), volleyball (Macquet, 2009), soccer (Kermarrec and Bossard, 2014), and ice hockey (Bossard et al, 2010;Mulligan et al, 2012). At least 80% of the experts' decisions were classified as simple-matching, which is consistent with the results of Klein' studies in work fields.…”
Section: Introductionsupporting
confidence: 73%
“…The RPD model started to be applied also in sport settings over the last years (e.g., Kermarrec and Bossard, 2014;Macquet, 2009;Mulligan et al, 2012;Neville et al, 2017) using the first-person approach to highlight how previous experiences organized the players' perception of one situation, and to bring new and complimentary empirical evidence on the way experts use surrounding information to support ongoing decisions and actions. Bossard et al (2010) and Macquet (2009) brought empirical evidence to complement Klein's four salient features categories: in an on-going situation, sport players take in account a plausible goal (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…Linking with the concept of Teamwork , is the Cognitive attribute Communication , which was also rated very highly and this is supported by research quantifying the communication instances (free kick/decision, umpire to player, or umpire to umpire communication), with an average of 2008 communications made by the field umpires per game. 6 The number of communications per game highlight effective communication by not only umpires to players, but also to other umpires, contributes to team success. Recent research has indicated effective communication is not always one way, with the ability to read and interpret player cues along with contextual factors also imperative.…”
Section: Discussionmentioning
confidence: 99%
“…Early studies in this cohort investigated the physical demands of officiating Australian football, 2,3 yet more recently the research has shifted to focus on cognitive components such as decision-making 4,5 and communication. 6 Several studies have recently examined the relationship between the physical and cognitive domains of officiating. 710 While these studies provide an understanding of the potential performance characteristics of Australian football umpires, there is no research presenting a framework identifying the importance of each attribute to the overall performance through the eyes of key stakeholders, such as elite umpires and their coaches.…”
Section: Introductionmentioning
confidence: 99%
“…Социологи обращались к таким аспектам судейства в регби, как толкование изменений правил [Kew, 1987], двигательная активность [Martin et al, 2001] и принятие решений в игровых ситуациях . Обширный каталог натуралистических исследований посвящен взаимодействию официальных представителей матча в регби [Mellick et al, 2005;Mellick et al, 2007] и в других игровых видах спорта [Neville et al, 2017]. Наконец, некоторые исследователи изучают применение технологий для вынесения решений судьями в спортивных играх [Kerr, 2016;Leveaux, 2010;Steen, 2011].…”
Section: исследовательская перспективаunclassified